Investigation of free radical scavenging activities of some Isatin Schiff bases (OH versus NH). A DFT Study - Habiba Boudiaf; Nadjia Latelli; Roumaissa Khelifi; Salima Hamadouche; Lynda Merzoud; Christophe Morell; Henry Chermette (Chemical Physics Impact)
In the present study we analyze various mechanisms of primary antioxidant action of a series of Schiff bases of isatin and its derivatives. For the purpose, theoretical calculations have been performed by means of density functional theory (DFT), using the hybrid functional M05–2X, range-separated functional LC-ωPBE and 6–31+G (d, p) basis set. The reactivity of these Schiff bases has been investigated and interpreted using chemical reactivity descriptors in gas and solvents phase. The two computational approaches used provide identical mechanisms trends in gas and non -polar phase and they are shown that the hydrogen atom transfer (HAT) mechanism is more favored. In contrast, the polarity of the solvent plays a crucial role in the antioxidant activity mechanism, as a higher solvent polarity enhances the contribution of the sequential proton loss electron transfer (SPLET) mechanism. It is found that the isatin group did not suppress the antioxidant effect of the disubstituted Schiff bases products as suggested by the experimental results.